2016
DOI: 10.1213/ane.0000000000001513
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Residual Neuromuscular Blockade, Oversedation, and Hypothermia on Adverse Respiratory Events in a Postanesthetic Care Unit: A Prospective Study of Prevalence, Predictors, and Outcomes

Abstract: The prevalence of RNMB in the PACU was >30%. Older age, open abdominal surgery, and duration of operation <90 minutes were associated with increased risk of RNMB in our patients. Our RR estimate for AREs was highest for depressed level of consciousness. When AREs occur in the PACU, potentially preventable causes including RNMB, hypothermia, and reduced level of consciousness should be readily identified and treated appropriately. Delaying extubation until the patient is awake and responsive may reduce AREs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 41 publications
4
42
3
Order By: Relevance
“…Naguib et al [5] reported that about 40% of patients undergoing general anesthesia with the use of neuromuscular blocking agent had TOF ratio of less than 0.9, and about 12% of patients in the PACU had TOF ratio of less than 0.7. Stewart et al [1] also reported that TOF ratio was less than 0.9 in 31% of patients in the PACU. In addition, old age, laparotomy, and short operation time (<90 minutes) were risk factors for residual neuromuscular blockade [1].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Naguib et al [5] reported that about 40% of patients undergoing general anesthesia with the use of neuromuscular blocking agent had TOF ratio of less than 0.9, and about 12% of patients in the PACU had TOF ratio of less than 0.7. Stewart et al [1] also reported that TOF ratio was less than 0.9 in 31% of patients in the PACU. In addition, old age, laparotomy, and short operation time (<90 minutes) were risk factors for residual neuromuscular blockade [1].…”
Section: Discussionmentioning
confidence: 93%
“…Stewart et al [1] also reported that TOF ratio was less than 0.9 in 31% of patients in the PACU. In addition, old age, laparotomy, and short operation time (<90 minutes) were risk factors for residual neuromuscular blockade [1]. In this patient, residual neuromuscular blockade effect may be considered because TOF ratio was 0.68 in the PACU.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations